2021
DOI: 10.1080/02705060.2021.1975580
|View full text |Cite
|
Sign up to set email alerts
|

Pollution profile of waterborne bacterial and fungal community in urban Rivers of Pearl River estuary: Microbial safety assessment

Abstract: Waterborne pathogens in urban rivers of estuarine areas pose a great threat to human health. In this study, both bacterial and fungal community structures of four urban rivers in the Pearl River estuarine area were investigated using high-throughput sequencing. Results showed that the diversity and richness indices of the bacterial community were higher than that of fungi. Taxonomic analysis indicated that the most abundant bacterial phylum was Actinobacteria, while the most abundant fungal phylum was Ascomyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…Matsuoka et al found similar results along a river network in Japan in 2019, where they found that fungal DNA assemblages had a spatial structure and samples that were closer to one another tended to be more similar. Overall, our results agree with the numerous studies of urban, eutrophic, and brackish freshwater bodies since proteobacteria, bacteroidetes, firmicutes, cyanobacteria, chloroflexi, actinobacteria, and acidobacteria were all well-represented [77][78][79][80]. The elevated presence of Verrucomicrobia and Gammaproteobacteria aligned more with the brackish metagenome [80].…”
Section: Discussionsupporting
confidence: 91%
“…Matsuoka et al found similar results along a river network in Japan in 2019, where they found that fungal DNA assemblages had a spatial structure and samples that were closer to one another tended to be more similar. Overall, our results agree with the numerous studies of urban, eutrophic, and brackish freshwater bodies since proteobacteria, bacteroidetes, firmicutes, cyanobacteria, chloroflexi, actinobacteria, and acidobacteria were all well-represented [77][78][79][80]. The elevated presence of Verrucomicrobia and Gammaproteobacteria aligned more with the brackish metagenome [80].…”
Section: Discussionsupporting
confidence: 91%
“…Matsuoka et al found similar results along a river network in Japan in 2019, where they found that fungal DNA assemblages had a spatial structure and samples which were closer to one another tended to be more similar. Overall, our results agree with numerous studies of urban, eutrophic, and brackish freshwater bodies since Proteobacteria, Bacteroidetes, Firmicutes, Cyanobacteria, Chloroflexi, Actinobacteria, Acidobacteria were all well-represented [66,67,68,69]. The elevated presence of Verrucomicrobia and Gammaproteobacteria aligned more with the brackish metagenome [69].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of low energy and currents from the waves in estuaries makes the pollutants accumulate in sediments instead of dispersing [10]. The types of pollutants found in estuaries are heavy metals [11,12], radionuclides [13], and pathogens such as bacterial pathogens [14], protozoa [15], enteric viruses [16], and fungus [14]. Furthermore, antibiotics, antibiotic resistant genes, and MPs are regarded as important emergent pollutants in the estuarine ecosystem due to their widespread distribution, persistence, and impact on the environment and human health [17].…”
Section: Introductionmentioning
confidence: 99%